Dynamic Linkages of Asian Emerging Stock Markets: An Analysis of the Pre- and Post-liberalization Era - Sarmidi, Tamat (1998)

(untitled)
The main purpose of this thesis is to assess the impact of removal of financial impediments on the ASIAN emerging equity markets. In the recent years the ASIAN countries have attempted to promote economic growth by taking steps to liberalise their domestic financial systems and removing restriction in international capital flows. countries, greater role in their financial markets. An important effect of financial liberalisation policies is the impact on the degree of integration between the emerging markets and the world equity markets. If equity markets are highly integrated, it implies that a given country's market cannot effectively insulate from foreign influences. linkages of the equity markets in the region with the major world markets by utilising the lohansen-luse tests, data is used in the analysis covering the period from January 1988 to January 1997. The ASIAN emerging markets selected include Malaysia, South Korea, Taiwan and Thailand while Hong Kong, Japan and the US are considered as the major world markets in vector autoregressive (VAR) model. The empirical evidence obtained from this study suggests the following. First, market liberalisation appears to have significant impact on all the equity markets. Analysis on iterative Johansen tests, sub-sample analysis and CUSUM tests indicate a possible structural break in the long run relationship among the emerging stock markets and the major exchange markets. Second, national stock markets are becoming more interdependent with the US, Japan and Hong Kong providing the link in the interdependence as one move towards the present liberalise system. Finally, the individual markets are all adjusting more rapidly to the equilibrium paths or stationary fundamental forces as one move towards recent past, and shocks to the system are becoming more persistent in the 1990's. The results of this study have some important policy conclusions. First, effective and efficient diversification of securities portfolios among international stock markets cannot be achieved given that the markets are cointegrated. Second, in an internationally integrated capital markets the scope for an independent monetary policy is limited. In fact if these countries insist on pursuing a dependent monetary policies the move may have a destabilising effect.